P054: The effectiveness of emergency department-based interventions for patients with advanced or end-stage illness: a systematic review. (May 2019) - Ghalab, A.; Kruhlak, M.; Kirkland, S.; Ruske, H.; Campbell, S.; Villa-Roel, C.; Rowe, B.
Abstract : Introduction : Patients with advanced or end-stage illness frequently present to emergency departments (EDs), many of whom are in need of palliative care (PC). Emergency physicians have struggled in providing high quality care to these patients and there is a need to identify cost-effective PC interventions delivered in the ED to improve patient outcomes. The objective of this systematic review was to examine the effectiveness of ED-based PC interventions.Methods : A comprehensive search of nine electronic databases and grey literature sources was conducted to identify any comparative studies assessing the effectiveness of ED-based PC interventions to improve health outcomes of patients with advanced or end-stage illness. Two independent reviewers completed study selection, quality assessment, and data extraction. Differences were mediated via third-party adjudication. Relative risks (RR) with 95% confidence intervals (CIs) were calculated using a random effects model and heterogeneity (I2) was reported.Results : From 5882 potentially eligible citations, 12 studies were included. Two studies are currently on-going clinical trials, and as such, 10 studies were included in this analysis. The studies consisted of before-after studies (n = 5), RCTs (n = 4), and an observational cohort (n = 1). Interventions assessed among the included studies consisted primarily of ED-directed PC consultations (n = 6), while other studies assessed screening of patients with advanced or end-stage illness and PC needs (n = 2), education on PC for ED-staff (n = 1), and an ED-based critical care unit (n = 1). Infrequent reporting of important outcomes (e.g., Mortality, ED relapse) limited the ability of this review to conduct meaningful meta-analysis. There was no difference in patient mortality between two studies assessing ED-directed PC consultations (RR = 0.89; 95% CI: 0.71, 1.13; I2 = 0%). One before-after study (RR = 0.73; 95% CI: 0.47, 1.13) and two RCTs (RR = 2.19; 95% CI: 0.40, 11.92; I2 = 96%) did not identify significant differences in PC consultations intervention (implementation of ED-directed PC consultations) and control (usual care) patients.Conclusion : This review found limited evidence to support the recommendation of any particular ED-based intervention for patients presenting to the ED with advanced or end-stage illness. High quality studies and standardized outcome reporting are needed to better understand the impact of PC interventions in the ED setting.